A Rare Case of Lichen Planus/Discoid Lupus Erythematosus Overlap Syndrome and Its Successful Treatment - Shehdev Meghwar; Muskan Batra; Noor Zehra Shabbir; Preety Devi; Ajeet Singh; Asma Ikram; Amogh Verma (Clinical Case Reports)
ABSTRACT An uncommon condition referred to as the overlap syndrome of lichen planus (LP) and lupus erythematosus (LE) exhibits immunopathological, histological, and clinical characteristics of both LP and LE. Though LP and LE are common individually, their overlap is rare. This condition typically presents with large, scaly, centrally atrophic lesions on the distal limbs, face, and trunk, often bluish‐red to hypopigmented in color. We describe a unique case of overlap syndrome between LP and discoid LE in a 30‐year‐old female patient presenting with lesions on her scalp, limbs, the dorsum of her hands, and oral mucosa. The lesions were neither painful nor warm to the touch. The diagnosis of overlap syndrome involving discoid LE and LP was confirmed through laboratory investigations and dermatological evaluation. Initial treatment with clobetasol propionate showed no significant improvement. Subsequently, the patient was prescribed 200 mg of azathioprine daily, along with the corticosteroid Deflazacort. Notable improvement in the lesions was observed after 4–5 weeks of follow‐up.